Rancang Bangun Prototype Sistem Monitoring Suhu, Kelembaban dan Intensitas Cahaya pada Tanaman Cabai Berbasis IoT - Muhammad Yasmin Nur Shahrosi; Alex Harijanto; Lailatul Nuraini (Universitas Indraprasta PGRI Jakarta, 2023)
Monitoring is a very important activitiy carried out in chili cultivation. A monitoring system on chili plants designed in the form of the Internet of Things (IoT) is an electronic device that can interact directly with users who use it for monitoring and controlling devices with the help of the internet. The creation of the chili plant monitoring based on the Internet of Things (IoT) can facilitate monitoring activities on chili plants to monitor temperature, humidity and light intensity in real time without having to come to the location of chili planters. This study uses quantitative descriptive research by describing the design of a prototype monitoring system for temperature, humidity and light intensity on chili plants based on IoT and describing the results of measuring temperature, humidity and light intensity on the prototype that has been made by researchers. The results of this prototype design have the main components, namely NodeMCU ESP8266, DHT 22 Sensor and BH1750 Sensor. The results obtained for measuring temperature, humidity and light intensity in this prototype show that the R square value on the DHT sensor for temperature and humidity is 0.949 and 0.870 while for the BH1750 sensor value for light intensity is 0.998. The R square value of the sensor is in the interval 0.80-1.00. The results of the calibration measurement carried out on this prototype are considered very valid. Field test results show the sensors and outputs obtained can function very well.